IMPLIKASI PENEBUSAN KRISTUS DALAM PENDIDIKAN KRISTEN [THE IMPLICATION OF CHRIST’S REDEMPTION ON CHRISTIAN EDUCATION] - Musa Sinar Tarigan (Universitas Pelita Harapan, 2019)
The challenge of Christian education today is how to implement biblical principles in the context of education properly to distinguish Christian education from other educational concepts. Christian education will have no true meaning without the work of Christ. This principle is important for answering various educational challenges that are incompatible with biblical truth. The role of Christian education is very important in the effort to implement God's truth in a world of creation that longs for freedom from slavery of sin. That's why Christian education must be holistic, rooted, grow, and bear fruit in Christ. This article aims to show that biblical truth must be the foundation of a holistic Christian education. This article uses literature research by examining the biblical concept of Christ's atonement and its implementation in the practice of Christian education. This research was carried out from 2018 until 2019, and concluded that Christ's atonement has very strong implications in the practice of biblical Christian education in realizing God's love for humans and restoring God's creation to His original purpose.BAHASA INDONESIA ABSTRAK: Tantangan pendidikan Kristen dewasa ini adalah bagaimana mengimplementasikan prinsip Alkitab dalam konteks pendidikan dengan benar untuk membedakan pendidikan Kristen dengan konsep pendidikan lainnya. Pendidikan Kristen tidak akan memiliki makna tanpa karya Kristus. Prinsip ini penting untuk menjawab berbagai tantangan pendidikan yang tidak sesuai dengan kebenaran Alkitab. Peran pendidikan Kristen sangat penting dalam upaya mengimplementasikan kehendak Allah dalam dunia ciptaan yang merindukan kemerdekaan dari perbudakan dosa. Itu sebabnya pendidikan Kristen harus holistis, berakar, bertumbuh, dan berbuah di dalam Kristus. Artikel ini bertujuan untuk menunjukkan bahwa kebenaran Alkitab harus menjadi landasan pendidikan Kristen yang holistis. Artikel ini menggunakan riset literatur dengan meneliti konsep Alkitab tentang penebusan Kristus dan implementasinya dalam praktek pendidikan Kristen. Riset ini dilaksanakan pada tahun 2018 hingga 2019, dan menyimpulkan bahwa karya penebusan Kristus memiliki implikasi yang sangat kokoh dalam praktek pendidikan Kristen yang alkitabiah dalam mewujudkan kasih Allah kepada manusia dan memulihkan ciptaan Allah kepada tujuan semula.